Comparable Bulk Radar Attenuation Characteristics Across Both Martian Polar Layered Deposits. Issue 11 (20th November 2022) - Abu Hashmeh, N.; Whitten, J. L.; Russell, A. T.; Putzig, N. E.; Campbell, B. A.
Abstract: The dust‐laden and predominantly water ice south polar layered deposits (SPLD) exhibit unique radar behavior at Shallow Radar (SHARAD) frequencies that is not seen in the NPLD. A vertically extensive scattering phenomenon leads to diffuse echoes that obscure radar stratigraphy within the SPLD, referred to as "fog." Here, we use 2‐D and 3‐D SHARAD data to measure the areal extent in which the SPLD basal interface can be identified. We also measure reflected power of SPLD basal reflectors and compare those values to ice thickness, regional geomorphology, and the presence of radar echo scattering, to constrain any influence these factors may have on the propagation of radio waves and detectability of the base. Approximately 33% of the area in which the basal interface is observed in Mars Advanced Radar for Subsurface and Ionosphere Sounding data is also detected in SHARAD data. As expected, basal power shows a negative correlation with ice thickness, but the effects of radar fog are less clear. Areas of "column" radar fog patterns exhibit higher average basal power values than regions without radar fog, and areas with only near‐surface radar fog have the lowest average basal power values. Our study results suggest that these diffuse echoes may not be associated with radio wave attenuation. Average loss tangent for the SPLD (0.0019 ± 0.0012) indicates no distinguishable difference from previously reported NPLD values in terms of bulk loss properties. We speculate that the SPLD's infrequent reflections compared to the NPLD may be due to the former's dust being less densely packed together to facilitate radar detection. Plain Language Summary: The interior structure of Mars' dusty, water ice polar caps can be observed using radar instruments currently in Martian orbit. We use cross section images called radargrams to observe the strength (brightness) of the signal reflected from cap's surface and interior layers. One of these instruments exhibits different behavior in radargrams between the two caps: the southern cap produces a mysterious fog‐like radar signal that is not seen in the north. We use the relative brightness between layers within the caps to determine if the radar fog is associated with a greater amount of signal loss. We do see more loss as ice thickness increases, but we don't find the same association with the presence of radar fog. Additionally, our inability to see the base of the cap in our data also does not appear to be related to radar fog. We find that both polar caps as wholes exhibit similar radar properties, despite looking very different in radargrams. We suggest that the southern cap may have less densely packed dust within its layering. Key Points: The occurrence of a fog‐like phenomenon in radargrams is not associated with diminished reflector detectability or enhanced signal loss Bulk loss tangents between the south polar layered deposits (SPLD) and NPLD are similar, indicating similar bulk radar properties Less frequent reflections in the SPLD might be due to dust being less densely packed relative to the NPLD